PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI BIRO UMUM UNIVERSITAS PERTAHANAN DI SENTUL, BOGOR - Anwar, Syaiful; Adyas, Dasmansyah; Muchammad Hamdani; ., Al Amin (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2022)
This study aims to determine 1) the effect of compensation on employee performance; 2) The Effect of Work Motivation on Employee Performance; 3) The Effect of Compensation and Work Motivation jointly on the Performance of Public Bureau Employees of the Defense University in Sentul Bogor. The research design used is Ex-post facto. The sampling technique in this study used saturated sampling method, the sample in this study were 77 employees. Data collection techniques used in this study were documentation and questionnaires. The data analysis technique used is multiple linear regression analysis. The results showed that: 1) There is a positive and significant effect of Compensation on Employee Performance with a correlation coefficient Rx1y of 0.474 and a coefficient of determination R2 x1y of 0.225, a tcount of 2.125 > ttable of 1.991. 2) There is a positive and significant effect of Work Motivation on Employee Performance with a correlation coefficient of 0.674 rx2y and a determination coefficient of 0.454 r2x2y, the price of tcount is 6.114 > ttable 1.991. 3) There is a positive and significant effect of Compensation and Work Motivation together on Employee Performance with a positive multiple correlation coefficient Ry(1.2) of 0.696 and a coefficient of determination R2 y(1.2) of 0.485, Fcount value of 5.440 > Ftable 2,14